Buy-outs in Family Firms: A Statistical Overview and Study of Value Creation - Feng, Ye (2011)
The aim of our research is to give an update on the research of Ball et al. (2008), and to carry on studying the statistical overview of the buy-outs/ins in family firms. In this respect, we have also compared the statistical overview of the buy-outs/ins in family firms to all buy-outs/ins. Secondly, with the inspiration from Migel et al. (2009), we examine how different factors (e.g. the source of buy-outs, the involvement of private equity investors and the type of buy-outs) affect the value creation in post-buyout companies. As such, we have a particular focus on how these factors influence the value creation in post-buyout of family firms.